Corrupt governments receive less bilateral aid: Governance and the delivery of foreign aid through non-government actors - Martin Acht; Toman Omar Mahmoud; Rainer Thiele (Kiel Institute for the World Economy (IfW), 2014)
A core result of the aid allocation literature is that the quality of governance in recipient countries does not affect the amounts of foreign aid received. Donor countries may still give aid to poorly-governed countries because of a dilemma they face: those countries most in need typically also lack proper institutions. This paper argues that donors try to resolve this dilemma by delivering aid through non-state actors. Using aid shares as well as absolute amounts of aid allocated through different channels and considering different dimensions of governance, we provide evidence that bypassing governments via NGOs and multilateral organizations is indeed a response to weak recipient state institutions. The effect is stronger in aid sectors where donors can more easily switch between channels, and for the group of donors that have been dubbed 'like-minded' to indicate their specific focus on recipient need.
Keywords: F35; D73; L31; F53; 330; aid allocation; aid channels; governance